Can inpatient multidisciplinary rehabilitation improve health-related quality of life in MS patients on the long term – The Danish MS Hospitals Rehabilitation Study. (December 2020) - Boesen, Finn; Nørgaard, Michael; Skjerbæk, Anders Guldhammer; Rasmussen, Peter Vestergaard; Petersen, Thor; Løvendahl, Brita; Trénel, Philipp
Background: Inpatient multidisciplinary rehabilitation (MDR) can improve health-related quality of life (HRQoL) in multiple sclerosis (MS) patients. However, the evidence of a long-term benefit is limited. Objectives: To investigate the long-term effectiveness of inpatient MDR on HRQoL in MS patients. Methods: We conducted a randomized controlled partial crossover trial with 427 MS patients. Results: Statistical significant long-term improvements in HRQoL were found in three of the six outcome measures at 12-month follow-up. Three in four suggested minimal clinically important differences (MCIDs) were unmet. Conclusion: These results indicate that the administration of inpatient MDR may lead to long-lasting improvements in HRQoL in MS patients.